(untitled) (Boston, [Mass.], 2007)
Corporate Finance, by Ross, Westerfield, Jaffe and Jordan was written to convey the most important corporate finance concepts and applications as a level that is approachable to the widest possible audience. The concise format, managerial context and design, and student-friendly writing style are key attributes in this text. We took the best from RWJ Fundamentals and RWJ Corporate to create a book that fits an underserved need in the market. RWJJ Core Principles strikes a balance by introducing and covering the essentials, while leaving more specialized topics to follow-up courses. This text distills the subject of corporate finance down to its core, while also maintaining a deciding modern approach. The well-respected author team is known for their clear, accessible presentation of material that makes this text an excellent teaching tool.
Keywords: Corporations,Tập đoàn; Finance,Tài chính